2009
DOI: 10.1677/joe-08-0363
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II enhances the increase in monocyte chemoattractant protein-1 production induced by tumor necrosis factor-α from 3T3-L1 preadipocytes

Abstract: Monocyte chemoattractant protein-1 (MCP-1) and angiotensin II (Ang II) in adipose tissue are thought to induce systemic insulin resistance in rodents; but the precise mechanism is not fully clarified. We examined the mechanism of Ang II-induced and/or tumor necrosis factor-a (TNF-a)-induced MCP-1 production from 3T3-L1 preadipocytes. The MCP-1 protein and MCP-1 mRNA expression in 3T3-L1 preadipocytes were increased significantly by stimulation with TNF-a. We found no significant increase in MCP-1 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that TNFα-induced MCP-1 gene expression in adipocytes or other cell types occurs via activation of the transcription factors NF-κB or AP-1 (i.e., c-Jun, c-fos, ATF), because the promoter of the MCP-1 gene contains NF-κB and AP-1 binding sites. 44,45 Indeed, we found that Q3G reduced TNFα-mediated phosphorylation of JNK and downstream c-Jun activation (Figure 4B), but not ERK activation or IκBα degradation (data not shown), in human primary adipocyte cultures. Further investigations examining upstream activators of TNFα-mediated inflammatory signaling are needed to understand how Q3G suppresses this pathway.…”
Section: ■ Discussionmentioning
confidence: 81%
“…It has been demonstrated that TNFα-induced MCP-1 gene expression in adipocytes or other cell types occurs via activation of the transcription factors NF-κB or AP-1 (i.e., c-Jun, c-fos, ATF), because the promoter of the MCP-1 gene contains NF-κB and AP-1 binding sites. 44,45 Indeed, we found that Q3G reduced TNFα-mediated phosphorylation of JNK and downstream c-Jun activation (Figure 4B), but not ERK activation or IκBα degradation (data not shown), in human primary adipocyte cultures. Further investigations examining upstream activators of TNFα-mediated inflammatory signaling are needed to understand how Q3G suppresses this pathway.…”
Section: ■ Discussionmentioning
confidence: 81%
“…Importantly, various adipocytes-derived chemokines increase monocyte recruitment into adipose tissue and the MCP-1/CCR2 pathway is known to play a crucial role in monocyte/macrophage infiltration into obese adipose tissue [30-32], suggesting the involvement of adipose MCP-1 in the prevention of the metabolic syndrome. Inflammatory cytokines, such as TNF-α, interleukin-1β (IL-1β), and transforming growth factor-β (TGF-β), increase MCP-1 through the activation of ERK, nuclear factor-κB (NFκB), and c-Jun N-terminal kinase (JNK) pathway [33-35]. In the course of adipocyte hypertrophy, ERK is activated while mitogen-activated protein kinase phosphatase-1 (MKP-1) is inactivated [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of ANG II signaling in adipocytes is related to the adipocyte production of inflammatory mediators and chemoattractant that cause low-grade adipose tissue inflammation, and obesity and insulin resistance are closely associated with a state of low-grade inflammation in adipose tissues (394). Data demonstrate that ANG II enhances TNF-␣-induced MCP1 expression in 3T3-L1 preadipocytes via a ERK1/2-and p38MAPK-dependent pathways (37). An ARB with PPAR␥ receptor agonist activity, telmisartan, attenuated the release of the proinflammatory factors secreted from 3T3-L1 adipocytes and improved lipid metabolism possibly via activation of the MAPK pathway and upregulation of eNOS/NOS3 and carnitine palmitoyltransferase 1␣.…”
Section: B Roles Of Ang II Receptor Signaling In Adipose Tissuementioning
confidence: 97%